2015
DOI: 10.1109/access.2015.2502220
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Detection via a Quantitative Radiomics-Driven Conditional Random Field Framework

Abstract: The use of high-volume quantitative radiomics features extracted from multi-parametric magnetic resonance imaging (MP-MRI) is gaining attraction for the autodetection of prostate tumors, since it provides a plethora of mineable data, which can be used for both detection and prognosis of prostate cancer. While current voxel-resolution radiomics-driven prostate tumor detection approaches utilize quantitative radiomics features associated with individual voxels on an independent basis, the incorporation of additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…From the literature review (Table 1), it can be seen that the different classifiers, namely bagging (Parmar et al, 2015b), Bayesian (Parmar et al, 2015b), boosting (Parmar et al, 2015b), classification and regression tree (CART) , decision tree (Hawkins et al, 2014;Chaudhury, 2015;Parmar et al, 2015b;Velazquez et al, 2015), discriminant analysis (Balagurunathan et al, 2014b;Coquery et al, 2014;Parmar et al, 2015b), generalised linear (Parmar et al, 2015b), K-nearest neighbour (K-NN) Chaddad et al, 2015;Parmar et al, 2015b;Lian et al, 2016;Wu et al, 2016), logistic regression (Guo et al, 2015;Parmar et al, 2015a;Vallières et al, 2015;Ypsilantis et al, 2015;Coroller et al, 2016;Huang et al, 2016;Liang et al, 2016), naïve Bayes (Chaudhury, 2015;Emaminejad et al, 2016;Wu et al, 2016), neural network (Parmar et al, 2015b), random forest (Parmar et al, 2015b;Wu et al, 2016), and support vector machine (SVM) Chaudhury, 2015;Chung et al, 2015;Depeursinge et al, 2015;Khalvati et al, 2015;Parmar et al, 2015b;Upadhaya et al, 2015aUpadhaya et al, , 2015bYpsilantis et al, 2015;…”
Section: Discussionmentioning
confidence: 99%
“…From the literature review (Table 1), it can be seen that the different classifiers, namely bagging (Parmar et al, 2015b), Bayesian (Parmar et al, 2015b), boosting (Parmar et al, 2015b), classification and regression tree (CART) , decision tree (Hawkins et al, 2014;Chaudhury, 2015;Parmar et al, 2015b;Velazquez et al, 2015), discriminant analysis (Balagurunathan et al, 2014b;Coquery et al, 2014;Parmar et al, 2015b), generalised linear (Parmar et al, 2015b), K-nearest neighbour (K-NN) Chaddad et al, 2015;Parmar et al, 2015b;Lian et al, 2016;Wu et al, 2016), logistic regression (Guo et al, 2015;Parmar et al, 2015a;Vallières et al, 2015;Ypsilantis et al, 2015;Coroller et al, 2016;Huang et al, 2016;Liang et al, 2016), naïve Bayes (Chaudhury, 2015;Emaminejad et al, 2016;Wu et al, 2016), neural network (Parmar et al, 2015b), random forest (Parmar et al, 2015b;Wu et al, 2016), and support vector machine (SVM) Chaudhury, 2015;Chung et al, 2015;Depeursinge et al, 2015;Khalvati et al, 2015;Parmar et al, 2015b;Upadhaya et al, 2015aUpadhaya et al, , 2015bYpsilantis et al, 2015;…”
Section: Discussionmentioning
confidence: 99%
“…This is done by further refining the results from RD-FM stage at voxel-resolution through a CRF framework (rADC-CRF) to reinforce the relative ADC map effect on the tumour region detection. Previously, it was reported [ 36 ] that a CRF framework can noticeably reduce the sparsely distributed tumour candidates on results produced by voxel-based approach. In our experiment, the CRF model is applied to relative ADC map and results show it further increases the specificity by reducing the number of false positive.…”
Section: Discussionmentioning
confidence: 99%
“…Conditional random fields were first proposed by Lafferty et al [ 34 ] and have previously been used for image labelling [ 35 ]. In addition, in [ 36 ], it was shown that CRF can be used to enforce the spatial constraints on prostate tumours such as compactness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed a tumor candidate identification algorithm that identifies the regions of concern and constructs a comprehensive radiomics feature model to detect the much-suspected cancer regions. Further on the subject of prostate cancer in [20], a novel approach for automatic prostate tumor detection using a radiomics-driven conditional random field (RD-CRF) is proposed. The proposed method analyses the inter-voxel spatial and radiomics feature relationships to ensure that the identified tumor candidates exhibit specific tissue characteristics of cancer.…”
mentioning
confidence: 99%